Técnicas de logoterapia como estrategia para afrontar la violencia psicológica en las relaciones de enamoramiento que mantienen los estudiantes del segundo año de bachillerato paralelo d, de la unidad educativa Adolfo Valarezo, 2019-2020 - Cartuche Robalino, Jose Antonio (2021)
Psychological violence in infatuation is a problem that is evident and faced by couples especially in the adolescent stage, this study will serve as support for future research and youth, facilitating the clear identification of it, so research was carried out: Logotherapy techniques as a strategy to deal with psychological violence in the relationships of infatuation maintained by students of the second year of parallel high school d, of the educational unit Adolfo Valarezo, 2019-2020. As a general objective was to propose speech therapy techniques as a strategy to deal with psychological violence in infatuation relationships. Exploratory, descriptive, non-experimental transverse cutting research, based on scientific, synthetic analytical, inductive, deductive method; the Subtle and Manifest Psychological Abuse Scale (SOPAS) was applied to the sample of 26 students. The results obtained, in relation to the subtle psychological violence those investigated, 31% maintain subtle psychological violence at a low level, 54% at an average level, while 15% maintain a high level of subtle psychological violence. In relation to manifest psychological violence it is found that 46% of adolescents maintain this violence at low levels, 50% receive this violence at an average level, and 4% of investigated people experience manifest psychological violence at a high level. These results present a methodologically structured proposal through workshops based on logotherapy techniques such as socratic dialogue, dereflection, confrontation and paradoxical intent, considering activities that promote a future confrontation and prevention of these violent behaviors during the stage of infatuation